Pembuatan Tepung Biji Durian sebagai Bahan Kue untuk Peningkatan Ketersediaan Pangan dan Promosi Kesehatan pada Ibu-Ibu di Desa Baning Kota Kecamatan Sintang - Juliansyah, Elvi; Haryanti, Yunida; Sohibun, Sohibun; Wagiran, Wagiran; Saragih, Septina Boru; Barsilia, Barly (Universitas Pahlawan Tuanku Tambusai, 2026)
Utilization of local food for family food security through processing durian seeds containing carbohydrates and processed as a substitute for wheat flour. Baning Kota Village, Sintang District, with abundant availability of durian fruit, its use as a food ingredient is not optimal. The aim is to improve the knowledge and skills of mothers in processing durian seeds into ingredients for making additional food supplies (AFS) cakes. The method of implementation of the activity was carried out through an educational approach in the form of demonstrations and direct practice of making durian seed flour and cake processing. The activity was carried out in Baning Kota Village, Sintang District, targeting Family Empowerment and Welfare (FEW) mothers. The results of the activity increased understanding of the nutritional value of durian seeds, the processing process, and the ability to make flour and cakes. The enthusiasm of the participants was evident from their active involvement during the activity and the ongoing discussions. This activity is effective as a community-based health promotion intervention and has the potential to support family food provision and improve nutritional status, especially for early childhood.